Genetic diversity and selection of heirloom tomato accessions based on the physical and biochemical fruit-related traits - Constantino,Leonel Vinicius (2022)
ABSTRACT Heirloom tomatoes are open-pollinated varieties bearing a wide diversity of colors and shapes that may be used by breeders aiming to improve physical and biochemical fruit traits. Hence, in this work heirloom tomato accessions were characterized, gathering information to genetic breeding programs focusing on human food. For that, 67 heirloom tomato accessions were evaluated for fruit size, fruit mass, fruit volume, color, vitamin C, titratable acidity, soluble solids content, phenolic compounds content, total flavonoid content, and antioxidant activity. The experiment was conducted in a randomized complete block design with three repetitions. Linear mixed model, Pearson’s correlation and hierarchical clustering were applied to data. Five groups were formed by Ward’s clustering method. The accession UEL 300 constituted group A, which had the greatest mass and volume fruit. Eight accessions formed group B and showed mostly yellow fruits. Group C was comprised of 13 accessions, which had the highest levels of carotenoids, vitamin C, and antioxidant activity. Thirty-three accessions that constituted group D did not stand out for any of the attributes, while 12 accessions into group E had the highest content of phenolic compounds and flavonoids, along with the highest ratio of soluble solids and acidity. Five accessions in this collection (UEL 296, UEL 146, UEL 238, UEL 231, and UEL 217) stood out for their biochemical traits. The wide diversity for physical and biochemical fruit traits can be explored in tomato breeding programs, seeking to develop new cultivars, and strengthening family farming.